2020
DOI: 10.3389/fphys.2020.617237
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Acid-Mediated TOR Pathway Regulates Reproductive Potential and Population Growth in Cyrtorhinus lividipennis Reuter (Hemiptera: Miridae)

Abstract: The predatory mirid bug, Cyrtorhinus lividipennis Reuter, feeds on brown planthopper (BPH) eggs that are deposited on rice and gramineous plants surrounding rice fields. The development and reproduction of C. lividipennis are inhibited by feeding on BPH eggs from gramineous species, and the underlining regulatory mechanism for this phenomenon is unclear. In the present study, HPLC-MS/MS analysis revealed that the concentrations of six amino acids (AAs:Ala, Arg, Ser, Lys, Thr, and Pro) were significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Previous studies indicated that TOR and Wnt/β‐cadherin pathways respond to elevated Ala concentrations, to modulate embryonic development, and to reduced fecundity in C. lividipennis , suggesting that Ala acts in the development and fecundity in C. lividipennis (Ge, Jiang, et al, 2020; H. Zhu et al, 2020). ALT (E.C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that TOR and Wnt/β‐cadherin pathways respond to elevated Ala concentrations, to modulate embryonic development, and to reduced fecundity in C. lividipennis , suggesting that Ala acts in the development and fecundity in C. lividipennis (Ge, Jiang, et al, 2020; H. Zhu et al, 2020). ALT (E.C.…”
Section: Discussionmentioning
confidence: 99%
“…The ClALT expressed sequence tag was found in the transcriptome of C. lividipennis (H. Zhu et al, 2020). The first‐strand cDNA was synthesized in 20 μl reaction mixtures having random hexamers and oligo dT primers at 37°C for 15 min using the PrimeScript RT Reagent Kit with gDNA eraser, and the second‐strand cDNA was synthesized in 20 μl reaction mixtures with random hexamers and oligo dT primers for 15 min at 37°C using the PrimeScript RT Reagent Kit with (TaKaRa).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these bugs also feed on lepidopteran pests such as Sesamia inferens , Cnaphalocrocis medinalis , and Chilo suppressalis [ 20 ]. The previous studies showed that the C. lividipennis adult females, when consuming the surrounding paddy fields of gramineous plants such as Echinochloa glabrescens , Leptochloa chinensis , Digitaria ciliaris , and Cynodon dactylon (containing BPH eggs, nymphs, and adults), showed a significant decrease of PSP expression level, while, on the other hand, when consuming rice plants (always containing BPH eggs, nymphs or adults) displayed up-regulation of PSP gene expression and enhanced fecundity [ 21 ]. Furthermore, studies have reported that C. lividipennis prefer feeding on rice plants with BPH eggs [ 22 ].…”
Section: Introductionmentioning
confidence: 98%
“…During reproduction, insects require a massive input of nutrients from food sources for egg development ( Terashima and Bownes, 2004 ; Attardo et al, 2005 ). The regulation of amino acid/target-of-rapamycin (AA/TOR) plays an important role in supplementing nutrients for egg development, with the corresponding pathway being well-maintained in insects ( Roy and Raikhel, 2011 ; Smykal and Raikhel, 2015 ; Zhu et al, 2020 ). As a sensor of cellular nutritional status, the AA/TOR could activate the secretion of insect insulin-like peptides (ILPs), which interact with the insulin pathway to modify the titers of the juvenile hormone (JH) and ecdysone, which control the reproduction process of insect females, involving yolk protein production (vitellogenesis) and egg maturation ( Smykal and Raikhel, 2015 ).…”
Section: Introductionmentioning
confidence: 99%